FURNITUR PADA INTERIOR WELLBEING DI HUNIAN LAHAN TERBATAS JAKARTA: FURNITURE FOR WELLBEING INTERIOR IN MINIM SPACE JAKARTA RESIDENTIAL - Farhan Rizaldi Azmi; Cama Juli Rianingrum; Krishna Hutama (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
Furniture for Wellbeing Interior in Minim Space Jakarta Residential. The economic limitations of Indonesian society make most people choose to live in minim space housing which has limited land. Limited land affects minimal space and wide access to the residence. This research is motivated by the problem of limited land occupancy. This research was carried out using a qualitative descriptive methodology and design thinking method, namely identifying problems involving users directly and presenting the results in a more structured data manner. The aim is to design furniture that can meet the needs of residents in activities in limited residential spaces so as to fulfill interior wellbeing. The furniture designed has a multifunctional design and suitable materials so that it can be easily used within limited space. Multifunctional furniture is designed to be of an appropriate size to be comfortable to use, using materials and finishing that are safe for the user, so that it can meet wellbeing criteria. Wellbeing is a reference for the concept of multifunctional furniture in order to create a comfortable interior for users.